Modelling Disease Risk Faktors for Covid-19 on District/City in West Sumatera - Vitratul Ilahi; Masrizal Masrizal; Syafrawati Syafrawati (Jurnal Kesehatan Masyarakat Andalas, 2022)
The chain of transmission of COVID-19 cases has been increased from day to day. Based on data from the Ministry of Health, the province of West Sumatra is ranked 3rd in Indonesia. This research is aimed to find out the modelling of risk factor of COVID-19 disease in district/city in West Sumatera. This research is an observational analytic study using secondary data in 2020 and multivariate analysis includes a cluster analysis, biplot analysis and discriminant analysis. The unit of analysis in this study are all districts / cities in West Sumatra and uses 6 factors that cause COVID-19 in West Sumatra. Grouping process yielded  three  clusters  of  districts  /  cities  based  on factors  causes  COVID-19. The different variable between clusters based on the result of discriminant analysis, namely; the number of elderly, the percentage of poor people and the population density. To that end, it is advisable to  West Sumatra Provincial Health Office in the implementation of eradication programs and disease prevention COVID-19 to implement disease management based on the characteristics of each region of each district / city.